Decision Support System for Business Location Selection: Integration of MCDM Methods - Rakhmat Sigit Widodo; Suhirman Suhirman; Nur Wening (Maneggio, 2026)
Business location selection is a critical strategic decision that significantly influences operational efficiency, cost structure, and long-term competitiveness. The increasing complexity of decision criteria requires structured approaches that integrate analytical methods and decision support technologies. This study aims to analyze the effectiveness of integrating Multi-Criteria Decision Making (MCDM) methods within a Decision Support System (DSS) for business location selection. The research adopts a quantitative approach with a Design Science Research framework, involving data collection through questionnaires, expert judgment, and secondary data. The analysis combines AHP for criteria weighting and TOPSIS for ranking alternative locations. The results indicate that the integrated DSS successfully generates clear and objective rankings, with the best location identified based on comprehensive evaluation of multiple criteria. The findings also demonstrate that the system effectively handles trade-offs between conflicting factors such as cost, accessibility, and infrastructure. In conclusion, the integration of MCDM methods within a DSS enhances decision accuracy, reduces subjectivity, and provides practical support for selecting optimal business locations in complex environments